1960
DOI: 10.1126/science.132.3423.349
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Size as Related to Interest Value of Visual Stimuli

Abstract: Increases in the size of the pupil of the eye have been found to accompany the viewing of emotionally toned or interesting visual stimuli. A technique for recording such changes has been developed, and preliminary results with cats and human beings are reported with attention being given to differences between the sexes in response to particular types of material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
439
3
8

Year Published

1967
1967
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(490 citation statements)
references
References 2 publications
21
439
3
8
Order By: Relevance
“…Hess & Polt, 1960), cognitive load (Kahneman & Beatty, 1966), and mental effort (Kahneman, 1973;Hess & Polt, Sequential action representation in infancy 15 1964). Whatever the exact interpretation of the measure, using it enables us to contrast acquisition contingent vs. non-contingent responses since all interpretations suggested that dilations should be larger for actions that require more processing (Verschoor et al, in press).…”
Section: Experimental Approachmentioning
confidence: 99%
“…Hess & Polt, 1960), cognitive load (Kahneman & Beatty, 1966), and mental effort (Kahneman, 1973;Hess & Polt, Sequential action representation in infancy 15 1964). Whatever the exact interpretation of the measure, using it enables us to contrast acquisition contingent vs. non-contingent responses since all interpretations suggested that dilations should be larger for actions that require more processing (Verschoor et al, in press).…”
Section: Experimental Approachmentioning
confidence: 99%
“…For these reasons, pupil dilation has been used as an indicator of automatic responses, including responses reflecting sexual arousal (Goldinger & Papesh, 2012;Laeng, Sirois, & Gredebäck, 2012). Pupils dilate more to sexual stimuli depicting an individual's preferred sex than to stimuli of the other sex or to non-sexual stimuli (Hess & Polt, 1960;Hess, Seltzer, & Shlien, 1965;. In fact, dilation to sexually preferred stimuli appears to be the strongest pupillary response elicited by stimuli (Laeng et al, 2012).…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 99%
“…The most widely cited, earliest studies using pupillometry were conducted by Hess and Polt [1][2]. They have reported that when people view stimuli that is interesting, confusing or contains emotional tones, their pupils will dilate more compared to visually similar, but otherwise neutral stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by simply subtracting the average value for each participant from all data points [40], performing a z-transformation [30] or providing the percentage of change compared to a baseline value [1]. This latter practice is prone to producing misleading results because it is greatly influenced by the chosen baseline value [41] and should be avoided.…”
Section: Metrics Derived From Pupil Diametermentioning
confidence: 99%